2020
DOI: 10.1016/j.desal.2020.114455
|View full text |Cite
|
Sign up to set email alerts
|

Forward osmosis membranes and processes: A comprehensive review of research trends and future outlook

Abstract: Recently, Forward Osmosis (FO) desalination process has been widely investigated as a potential technology that could minimize the drawbacks of traditional desalination processes.To review the past, current, and future research scope of the FO desalination process, a statistical analysis that gives insights on the FO topics of interest is needed to assist researchers in the development of the FO technology. The main objective of this work is to conduct a Highlights 1-Research trends in forward osmosis technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(118 citation statements)
references
References 114 publications
1
111
0
Order By: Relevance
“…For emerging osmotic membrane processes such as forward osmosis (FO) and pressure retarded osmosis (PRO), the development of SWMs is still at an early stage and is only limited to lab-scale studies [ 5 , 6 , 7 , 8 ]. Although some researchers report that the hollow fibre membrane configuration is more suitable for FO and PRO processes due to its higher packing density, self-mechanical support properties and better flow control on both sides of the membrane (i.e., lumen and outer surface of fibre) [ 9 , 10 ], a large number of studies published over the years have used flat sheet membranes for assessing FO and PRO processes [ 6 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For emerging osmotic membrane processes such as forward osmosis (FO) and pressure retarded osmosis (PRO), the development of SWMs is still at an early stage and is only limited to lab-scale studies [ 5 , 6 , 7 , 8 ]. Although some researchers report that the hollow fibre membrane configuration is more suitable for FO and PRO processes due to its higher packing density, self-mechanical support properties and better flow control on both sides of the membrane (i.e., lumen and outer surface of fibre) [ 9 , 10 ], a large number of studies published over the years have used flat sheet membranes for assessing FO and PRO processes [ 6 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are not sufficient for wastewater treatment due to their operational efficiency parameters. These commercialized CA and CTA membranes provide low permeability, low salt rejection, poor resistance to biological species, and limited chemical stability [28]. PS, or PES, is another material use to fabricate FO membranes.…”
Section: Forward Osmosis Membranesmentioning
confidence: 99%
“…Recent studies have demonstrated that a lack of applied hydraulic pressure and optimization of the system's hydrodynamics can lead to less fouling and the higher reversibility of fouling [15,[29][30][31][32]. Due to the low flux that can be obtained in FO, there is more opportunity for low fouling [28,32,33]. Because of this, a more extensive range of pollutants can be removed from FS.…”
Section: Advantages Of Fo Membranesmentioning
confidence: 99%
“…Furthermore, as an emerging novel desalination technology, FO has undergone significant development during the past decades, due to its high energy efficiency and favorable separation performances [68]. Interested readers are referred to the excellent review literature on FO [69][70][71].…”
Section: Novel Technologiesmentioning
confidence: 99%